Pyloric motor function during emptying of a liquid meal from the stomach in the conscious pig. - Treacy, P J (1990)
1. In six conscious pigs antral, pyloric and duodenal pressures were recorded with a 5.5 cm sleeve sensor and multiple perfused side holes. The manometric assembly was positioned by dual point transmucosal potential difference measurement. Gastric emptying was measured by drainage of the proximal duodenum through a Thomas cannula. Pressures were correlated with emptying of ingested radiolabelled 5% dextrose. Alteration of emptying was produced by infusion into the more distal duodenum of nutrient and non-nutrient solutions of differing osmolalities. 2. Motor activity of the pylorus and antrum was stimulated by ingestion and modulated by intraduodenal infusion. Duodenal infusion of normal saline was associated with antro-pyloric pressure waves and rapid emptying of the ingested liquid. Duodenal infusion of dextrose, fatty acid, amino acids and hyperosmolar saline was associated with stimulation of isolated pyloric pressure waves, suppression of antral pressure waves and slowing of gastric emptying. 3. The dose-response relationship of these effects was investigated using varying rates of intraduodenal dextrose infusions. The emptying rate of the ingested liquid was inversely related to the rates of delivery of dextrose to the duodenum, directly related to the rate of antro-pyloric pressure waves and inversely related to the rate of isolated pyloric pressure waves. 4. Clearly defined episodes of pulsatile flow produced slightly more than half of the total emptying that occurred. This pulsatile flow was intimately associated in time with antro-pyloric pressure waves. Sequences of isolated pyloric pressure waves were associated with near cessation of emptying. When there were periods of absent pyloric antral pressure waves, flow rates intermediate between the rapid emptying of pulsatile flow during antro-pyloric pressure waves and the near cessation of flow during isolated pyloric pressure waves occurred. 5. The findings suggest a major role for the pylorus in the control of emptying of liquids from the stomach, both as a component of an antro-pyloric peristaltic pump and as a resistor to transpyloric flow during nutrient and hyperosmolar stimulation of duodenal receptors.